5-Azacytidine Promotes an Inhibitory T-Cell Phenotype and Impairs Immune Mediated Antileukemic Activity. (13th March 2014) - Stübig, Thomas; Badbaran, Anita; Luetkens, Tim; Hildebrandt, York; Atanackovic, Djordje; Binder, Thomas M. C.; Fehse, Boris; Kröger, Nicolaus
Abstract : Demethylating agent, 5-Azacytidine (5-Aza), has been shown to be active in treatment of myeloid malignancies. 5-Aza enhances anticancer immunity, by increasing expression of tumor-associated antigens. However, the impact of 5-Aza immune responses remains poorly understood. Here, T-cell mediated tumor immunity effects of 5-Aza, are investigated in vitro and in vivo . T-cells from healthy donors were treated with 5-Aza and analyzed by qRT-PCR and flow cytometry for changes in gene expression and phenotype. Functionality was assessed by a tumor lysis assay. Peripheral blood from patients treated with 5-Aza after alloSCT was monitored for changes in T-cell subpopulations. 5-Aza treatment resulted in a decrease in CD8+ T-cells, whereas CD4+ T-cells increased. Furthermore, numbers of IFN- γ + T-helper 1 cells (Th1) were reduced, while Treg-cells showed substantial increase. Additionally, CD8+ T-cells exhibited limited killing capacity against leukemic target cells. In vivo data confirm the increase of Treg compartment, while CD8+ T-effector cell numbers were reduced. 5-Aza treatment results in a shift from cytotoxic to regulatory T-cells with a functional phenotype and a major reduction in proinflammatory Th1-cells, indicating a strong inhibition of tumor-specific T-cell immunity by 5-Aza.